Researching migration methods, entropy and energy diagram to process ground penetrating radar data - Thanh, Van Nguyen; Nguyen, Thuan Van; Dang, Trung Hoai; Vo, Triet Minh; Vo, Lieu Nguyen Nhu (Vietnam Journal of Marine Science and Technology, 2017)
Electromagnetic wave velocity is the most important parameter in processing ground penetrating radar data. Migration algorithm which heavily depends on wave velocity is used to concentrate scattered signals back to their correct locations. Depending wave velocity in urban area is not easy task by using traditional methods (i.e., common midpoint). We suggest using entropy and energy diagram as standard for achieving suitable velocity estimation. The results of one numerical model and areal data indicate that migrated section using accurate velocity has minimum entropy or maximum energy. From the interpretation, size and depth of anomalies are reliably identified